Rhabdias bufonis (Rhabdiasidae) from the lung of the African common toad, Amietophrynus regularis (Bufonidae) in Egypt: new data on the basis of light and scanning electron microscopic study - Morsy, Kareem; Mohamed, Sara Ali; Abdel-Ghaffar, Fathy; El-Fayoumi, Hoda; Abdel-Haleem, Heba (PeerJ, 2018)
Background and Aims Rhabdias sp. (Rhabdiasidae) is a nematode parasite of family Rhabdiasidae infecting the lung of amphibians. The present study provides new morphological details for Rhabdias bufonis isolated from the lungs of the African common toad, Amietophrynus regularis based on observations of light and scanning electron microscopy (SEM). Methods Forty specimens were collected from its natural habitat: the damp, moist fields and gardens at Giza governorate, Egypt. Worms were isolated from the lungs, fixed and then preserved. They were examined using light and SEM with further line drawings. Results Fourteen specimens (35%) were found to harbor Rhabdias with an intensity of three to five worms per host. Bodies of the gravid females were elongated, slender, measured 3.22–9.86 (5.64 ± 0.03) long and 0.09–0.48 (0.23 ± 0.02) wide at mid-length. Buccal capsule was with cylindrical lumen and sclerotized walls. Ovaries were almost straight. The uteri were located anterior and posterior to the vulva. Uterus were filled with a large number of eggs (17–42). Eggs were oval in shape and some of them were with fully developed larvae inside. The tail was comparatively short, gradually tapered. SEM showed that worms possessed an oval anterior end with a simple, slit like oral opening. The lipless edges of the mouth opening were bordered with tiny cuticular elevations, radiated outwards. Two pairs of submedian cephalic papillae were observed around the oral opening as well as two amphids. Conclusion The current study presents new morphological details for R. bufonis isolated from the African common toad. Also, the morphology of the slit-like mouth opening, the two pairs of cephalic papillae, two amphids and the three pairs of cuticular elevations supporting the area around mouth opening were investigated.
Keywords: Rhabdias bufonis; Nematoda; Amietophrynus regularis; Bufonidae; Cuticular elevations; Cephalic papillae; Morphology; Morphometry